2005
DOI: 10.1002/marc.200500253
|View full text |Cite
|
Sign up to set email alerts
|

Macromolecular Recognition by Polymer‐Carrying Cyclodextrins: Interaction of a Polymer Bearing Cyclodextrin Moieties with Poly(acrylamide)s Bearing Aromatic Side Chains

Abstract: Summary: The interaction of a polymer bearing β‐cyclodextrin moieties (β‐CD polymer) with poly(acrylamide)s bearing aromatic side chains was investigated by viscometry to study the effect of collectivity (i.e., interactions at multi‐sites) in macromolecular recognition. The formation of inclusion complexes at multi‐sites caused a large difference in the size of interpolymer aggregates, even though the difference in association constants for complexation of native β‐CD with guest moieties was not very much larg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0
1

Year Published

2006
2006
2017
2017

Publication Types

Select...
4
3
1

Relationship

4
4

Authors

Journals

citations
Cited by 35 publications
(24 citation statements)
references
References 12 publications
1
22
0
1
Order By: Relevance
“…[36] CDs are able to recognize aromatic side-chains on a polymer chain. [37] Spectroscopic studies were reported for the interactions of CDs with naphthyl groups attached to poly(acrylamide). [38] Hashidzume and Harada et al studied the interactions of poly(methacrylamide)s bearing hydrophobic amino acid residues with CDs.…”
Section: Side-chain Recognitionmentioning
confidence: 99%
See 1 more Smart Citation
“…[36] CDs are able to recognize aromatic side-chains on a polymer chain. [37] Spectroscopic studies were reported for the interactions of CDs with naphthyl groups attached to poly(acrylamide). [38] Hashidzume and Harada et al studied the interactions of poly(methacrylamide)s bearing hydrophobic amino acid residues with CDs.…”
Section: Side-chain Recognitionmentioning
confidence: 99%
“…However, the gel turned into a sol upon addition of α‐CD, because α‐CD can incorporate a dodecyl group, which decreases the hydrophobic interactions between dodecyl groups . CDs are able to recognize aromatic side‐chains on a polymer chain . Spectroscopic studies were reported for the interactions of CDs with naphthyl groups attached to poly(acrylamide) .…”
Section: Side‐chain Recognitionmentioning
confidence: 99%
“…A variety of polymer-CD systems have been synthesized and they have been shown to exhibit self threading or associative properties. 118,[151][152][153] In a poly[(methyl vinyl ether)-alt-(maleic acid)]-g-b-CD (P(MVE-AM)-g-b-CD) and PEO-Adamantyl (Ad 3 ) system, strong inter-chain associations due to the complexation between PEO-Ad 3 and CDs were reported. At low pH values, where all COOH groups were protonated, additional hydrogen bonding between the PEO backbone of PEO-Ad 3 and the COOH groups of P(MVE-AM)-g-b-CD contributed to the associative properties.…”
Section: Ph-responsive Inclusion Complexesmentioning
confidence: 99%
“…[2] As a result, we have reported some examples of the selectivities enhanced by: (i) the steric effect of the polymer main chain, [3] (ii) the multi-site interaction, [4] and (iii) the competition with polymer micellization. [5] In this study, we have chosen adamantyl (Ad) and adamantylphenyl (AdPh) groups as guest moieties (Scheme 1) because it is known that the pair Interaction of b-cyclodextrin (b-CD) with alternating copolymers (pAdMA and pAdPhMA) of sodium maleate with adamantyl (Ad) and with adamantylphenyl (AdPh) vinyl ether has been investigated by several NMR techniques.…”
Section: Introductionmentioning
confidence: 99%